Improved binding site assignment by high-resolution mapping of RNA-protein interactions using iCLIP - Hauer, Christian; Curk, Tomaz; Anders, Simon; Schwarzl, Thomas; Alleaume, Anne-Marie; Sieber, Jana; Hollerer, Ina; Bhuvanagiri, Madhuri; Huber, Wolfgang; Hentze, Matthias W.; Kulozik, Andreas (Nature Communications, 2015)
Individual-nucleotide resolution crosslinking and immunoprecipitation (iCLIP) allows the determination of crosslinking sites of RNA-binding proteins (RBPs) on RNAs. iCLIP is based on ultraviolet light crosslinking of RBPs to RNA, reverse transcription and high-throughput sequencing of fragments terminating at the site of crosslinking. As a result, start sites of iCLIP fragments are expected to cluster with a narrow distribution, typically representing the site of direct interaction between the RBP and the RNA. Here we show that for several RBPs (eIF4A3, PTB, SRSF3, SRSF4 and hnRNP L), the start sites of iCLIP fragments show a fragment length-dependent broader distribution that can be shifted to positions upstream of the known RNA-binding site. We developed an analysis tool that identifies these shifts and can improve the positioning of RBP binding sites.
Gesehen am 14.07.2020